Acciones de enfermería en el parto humanizado en pacientes que acuden al Centro de Salud “Vinchoa” del Cantón Guaranda, Provincia de Bolívar en el periodo octubre 2019-marzo 2020 - Chazo Gáleas, Elisa Maribel (2020)
Humanized childbirth allows women to have the possibility of enjoying a decent birth, where their rights are respected; therefore nursing actions play a fundamental role. The objective of the research was to evaluate the fulfillment of nursing actions in the promotion of humanized childbirth, because it has been proven that the level of knowledge about natural birth is not adequate. The study was carried out in 55 pregnant women who attended the Vinchoa Health Center of the Guaranda canton. The methodology applied corresponds to a qualitative-quantitative approach, because information obtained through indicators was processed; the type of investigation was field, descriptive and transversal, and the inductive and descriptive method was used, with the interview and observation techniques, applied through the instruments, the Questionnaire and Observation Guide; which allowed data collection. The results show that the actions of are not being fully implemented, educational talks and information about procedures of humanized delivery are not provided; only 5.5% have received some type of information; and only 3.6% have been oriented; the level of knowledge in the patients is low, represented 38.2%, 40% of the women had a normal delivery and 20% ceased; In addition, nursing professionals almost always comply with the care protocol. It is concluded that the main nursing actions for the promotion of humanized childbirth if they are executed, but not continuously, the level of satisfaction of the mothers regarding the care received is good.